Hak Cipta dan Kepemilikan Hak Cipta atas Street Art yang Melekat Pada Properti Milik Orang Lain: Sebuah Dualisme Hukum - Jennifer Moniq Sutanto; Mas Rahmah; Xavier Nugraha (Fakultas Hukum Universitas Udayana, 2023)
Street art is a work of art on the streets, which is usually in the form of graffiti or murals. Street art is generally made on other people's property without permission. This is what raises the problem of copyright protection and ownership of street art because there is a conflict between copyright and property rights and making street art without permission is a form of vandalism. Therefore, there is still debate about copyright protection for street art and there is still legal dualism in this regard. This paper aims, firstly to provide an analysis regarding copyright protection for illegal street art and secondly to analyze the ownership of street art attached to the property of other people. The research method of this paper is normative using statutory, comparative, case, and conceptual approaches. The results of this article are first, even though street art is an illegal act because it is vandalism, there is still copyright protection in it. Second, even though it is related to copyright ownership of street art, it remains with the Street Art Artists because it is their copyright, but the property rights of the owner of the property must also be protected.